2010
DOI: 10.2224/sbp.2010.38.7.895
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation Criteria for Personal Trainers: An Analytical Hierarchy Process Approach

Abstract: Not only are personal trainers the face of the personal fitness industry, they also generate a significant portion of revenue in this multi-billion dollar business. It is therefore essential to produce the best possible personnel. In order to assist the industry in selecting the best trainers, we developed a preliminary personal trainer evaluation system based on a survey of experts. The analytic hierarchy process (AHP) method was then applied to the system. Of the three major dimensions -achievement, teaching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 2 publications
1
19
0
2
Order By: Relevance
“…Moreover, like other groups of practitioners within the field of kinesiology, the role has been continually shifting to meet new and emerging practice expectations. For example, evidence shows that personal trainers routinely take on a multitude of roles, including those of teacher, trainer, counselor, coach, supervisor, supporter, nutritionist, biomechanist, bodybuilding evaluator and consultant, life management advisor, weight controller, personal life consultant, business person, and physical fitness advocate (Chen, 2006;Chiu, Lee, & Lin, 2010;McKean, Slater, Oprescu, & Burkett, 2015;Smith Maguire, 2001. In this context, it can be noted that very few forms of regulation exist to restrict the types of work they undertake in practice environments.…”
Section: Issue 2: Ambiguous Role and Practice Expectationsmentioning
confidence: 99%
“…Moreover, like other groups of practitioners within the field of kinesiology, the role has been continually shifting to meet new and emerging practice expectations. For example, evidence shows that personal trainers routinely take on a multitude of roles, including those of teacher, trainer, counselor, coach, supervisor, supporter, nutritionist, biomechanist, bodybuilding evaluator and consultant, life management advisor, weight controller, personal life consultant, business person, and physical fitness advocate (Chen, 2006;Chiu, Lee, & Lin, 2010;McKean, Slater, Oprescu, & Burkett, 2015;Smith Maguire, 2001. In this context, it can be noted that very few forms of regulation exist to restrict the types of work they undertake in practice environments.…”
Section: Issue 2: Ambiguous Role and Practice Expectationsmentioning
confidence: 99%
“…Satty (1980) suggested that CI = 0 represents the survey takers' consistency before and after the assessment of the decision factor, signifying that there are no discrepancies between the two, while CI = 0.1 is the permissible error tolerance. When CI = 0.1 the consistency of the matrix is satisfactory, and thus it can be said that the whole evaluation process reaches consistency (Chiu et al, 2010). In this study, the CR of the whole matrix is 0.07, and thus is acceptable and satisfactory.…”
Section: Examining Consistencymentioning
confidence: 54%
“…The Delphi method not only enables the collection of wide and numerous evaluation standards, but also maintains the quality of individual expert judgment [4]. However, since opinions are often expressed with adjectives such as "good" or "bad", some level ambiguity is likely to result from the Delphi process.…”
Section: Fuzzy Delphi Methods (Fdm)mentioning
confidence: 99%